Labyrinth - Coulter, Catherine (New York : Gallery Books, 2019)
The #1 New York Times bestselling FBI Thriller series returns with another tour de force in which Agent Sherlock risks losing her career--and her sanity--over a case that is more complicated and twisted than any she's ever encountered.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Suspense fiction